Loss Given Default: Estimating by the Conditional Minimum Value - Ammari, Mustapha; Lakhnati, Ghizlane (International Journal of Economics and Financial Issues, 2017)
The Basel Committee offers banks the opportunity to estimate Loss Given Default (LGD) if they wish to calculate their own value for the capital required to cover credit losses. The flexibility to determine LGD values tailored to a bank's portfolio will likely be a motivation for a bank to want to move from the foundation to the advanced Internal Ratings-Based (IRB) approach. The importance of estimating LGD stems from the fact that a lender's expected loss is the product of the probability of default, the credit exposure at the time of default and the LGD. The Mertonian approach is used for LGD estimation. In this paper, we estimated the (LGD) parameter, using the Merton model, by the introduction of a new parameter which called the conditional minimum value. Four components have been developed in this work: estimation of Conditional Minimum, estimation of the loss given default LGD, development of a practical component, and finally validation of the proposed model. Keywords: Credit Risk Modeling, Loss Given Default, Rating Model, Basel 2, Merton's model, Backtesting. JEL Classifications: G17, G21, G24, G28, G32, G38